Work, unemployment, and leisure - Deem, Rosemary (Society now., 1988)
A concise introduction to contemporary issues surrounding work, leisure, and unemployment. Deem includes work both within and outside the formal economy. She concludes with a discussion about the future of work and leisure in industrial society.